Principals' Academic Supervision in Strengthening Teachers' Pedagogical Competence for Deep Learning Implementation - Jainatin Halomaon Hrp; Muhammad Fadhli (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
As the principal pedagogical approach within Indonesia's Kurikulum Merdeka (Independence Curriculum), deep learning requires adequate teacher pedagogical competence to ensure that learning unfolds in a mindful, meaningful, and joyful manner. However, prior studies have tended to examine principals' academic supervision and deep learning implementation as separate domains, leaving limited insight into how supervision can be specifically designed to support deep learning, particularly in Islamic-based schools. This study aims to describe and critically analyze the planning, implementation, and follow-up of principals' academic supervision in strengthening teachers' pedagogical competence for deep learning implementation at SMP An-Nizam, Medan. The study employed a qualitative approach with a descriptive case study design, involving one principal, one vice-principal for curriculum affairs, and three subject teachers selected as informants through purposive sampling. Data were collected through semi-structured interviews, non-participant observation, and documentation study, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing; data trustworthiness was established through source and technique triangulation. The findings indicate that supervision planning was carried out systematically through scheduled and incidental pathways, preceded by teacher competence strengthening and supported by deep-learning-based instruments; supervision implementation involved classroom observation, CCTV monitoring, multi-party collaboration, and reflective feedback; while follow-up was realized through mentoring, training, periodic evaluation, and the provision of appreciation. The critical analysis reveals that although supervisory practice at SMP An-Nizam is relatively comprehensive, the use of CCTV monitoring risks generating a performative impression that is not fully consistent with the principles of clinical supervision, which emphasize collegial, non-evaluative relationships. This study establishes its novelty by integrating the concepts of principals' academic supervision and deep learning implementation within a single, coherent framework at an Islamic-based secondary school a focus that remains limited in the existing literature while also offering critical reflection on the boundary between surveillance and professional development in contemporary supervisory practice.